(3GdfhGOQ aj JMGhjd GdSfjfs - (3LYaQ Hf eMeO Hf YeQ GdHdNj, CHh eYTQ , nCoHh nerYnTQ Gdnandcj,J (B272 (3g` s ((3MGLi Ydi GdQGRi s)
(3ChdgG (B:s
(3bGd GdMcje Ef cd TF jHJOC Hg ai GdGLJeGY cGf fbUg ef GdESJbHGd hcdeG cGf ef GdGSJbHGd GHJOGDg cGf fbUg ef GdGLJeGY s
(3BNQgG (B:s
(3hYdi Gf GdMGOK ef Gddg Ohf GdedI dGJUGd GdOQLI HWGdYZ GdbQGf GdOGd Ydi GdGSJaJGM GdChd YhOI GdbQGf HQL GdKhQ hYfO YhOI GdbQGf dehVYg GdCUdi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGHYs
(3HgG fXGe GdJYbjHIs
(3cJHJ fbdkG Yf fSNI LeYgG GHQGgje GdMGSH GdeGdci GdefUhQi GdfGUQi HeOjfI GdbGgQI (B759 (3hHChd GdeLehYI Jedc SfI (B1249s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B127 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B148s
Keywords: (3Gdadcs